Achieving end-to-end success in the clinic: Pfizer's learnings on R&D productivity. Issue 3 (March 2022) - Fernando, Kathy; Menon, Sandeep; Jansen, Kathrin; Naik, Prakash; Nucci, Gianluca; Roberts, John; Wu, Shuang Sarah; Dolsten, Mikael
Highlights: Pfizer achieved an industry leading end-to-end clinical success rate of 21%. Significantly higher than peer average of 11% and representing a 10-fold increase from 2% in 2010. Enhanced data-driven decision making was a key enabler. The R&D turnaround laid the foundation for the rapid development of COVID-19 vaccine and the antiviral candidate Paxlovid under the "lightspeed" paradigm. Abstract: Over the past decade, Pfizer has focused efforts to improve its research and development (R&D) productivity. By the end of 2020, Pfizer had achieved an industry-leading clinical success rate of 21%, a tenfold increase from 2% in 2010 and well above the industry benchmark of ∼11%. The company had also maintained the quality of innovation, because 75% of its approvals between 2016 and 2020 had at least one expedited regulatory designation (e.g., Breakthrough Therapy). Pfizer's Signs of Clinical Activity (SOCA) paradigm enabled better decision-making and, along with other drivers (biology and modality), contributed to this productivity improvement. These laid a strong foundation for the rapid and effective development of the Coronavirus 2019 (COVID-19) vaccine with BioNTech, as well as the antiviral candidate Paxlovid™, under the company's 'lightspeed' paradigm.